PENERAPAN AGILE METHOD DAN BMC PADA STARTUP UMKMEKSPOR.ID SEBAGAI USAHA PENINGKATAN EKSPOR PRODUK UMKM PERTANIAN DAN AGRO INDONESIA DALAM MASA PANDEMI - Tiawan; I Gede Juliana Eka Putra; Alexandra Priscillia Devina (Jurnal Informatika Teknologi dan Sains, 2022)
MSMEs are currently booming in collaboration with innovative startups. According to the Assistant Governor of the BI Department of Economic and Monetary Policy Mr. Dody Budi Waluyo, there are have 3 problems related to agriculture, including production, distribution, and price affordability. This research uses Agile and BMC (Business Model Canvas) methods. Agile is a system development method that helps users/users so that the results obtained and in line with user needs, while BMC is a 9-component business model. The stages used in this study use the Agile model from Kanban to help see which processes will be implement,which proces are ongoing and which have been complete. It's hoped that the application of Agile and BMC methods can help solve the 3 main problems that exist in Indonesian its mean agriculture, especially in UMKMEkspor.id startups.